Strategi Branding PT Pupuk Kujang dalam Pembentukan Citra melalui Akun Instagram @pupukkujang - Habibah, Dian; Kusumaningrum, Rasti; Teguh Santoso, Made Panji (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Currently, many companies are competing to build their image through social media platforms like Instagram. PT Pupuk Kujang is also using Instagram for branding and engaging with the public to maintain the company's existence. This research aims to uncover PT Pupuk Kujang's branding strategy using the concept of The Circular Model of Some by Regina Luttrell. The research method employed is qualitative with a descriptive approach. It utilizes interview, observation, and documentation techniques. The research findings indicate that in the